KETERLIBATAN ORANG TUA DALAM PENDIDIKAN SEKS ANAK USIA DINI - Wahyuningsih, Riris; Putri, Habibah Afiyanti; Arini Haq, Bella; Rachmy Diana, Raden (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
The phenomenon of sexual violence against children in Indonesia, which has increased by 300% in the last decade, demands a preventive approach through early childhood sexuality education, yet still faces strong cultural resistance. This research explores the dynamics of parent-teacher collaboration in implementing early childhood sexuality education at TK Tunas Harapan Banyuwangi, focusing on paradigm transformation, collaborative mechanisms, and their impact on children's protective understanding. Employing qualitative educational ethnography with an interpretive-constructivist paradigm, the study involved 12 parents, 6 teachers, and 1 principal during March-June 2024. Data were collected through participatory observation, semi-structured interviews, focus group discussions, and document analysis, then analyzed using the Miles model with triangulation for validity. Findings reveal paradigm transformation from resistance to acceptance through andragogy-based